EFEKTIVITAS JALUR DISTRIBUSI PENJUALAN JERUK MANISDI KECAMATAN DAU, KABUPATEN MALANG - Farah Mutiara; Dwi Asnawi Nurhantanto (Universitas Tribhuwana Tunggadewi, 2016)
Orange is one type of fruit that is highly favored by the people. Citrus marketing is a whole system of business activities aimed at planning, pricing, promoting and distributing goods and services that can satisfy the needs of both the buyers there maupum potential buyers. Marketing itself serves to connect producers with consumers or also known as distributions. Distribution is the most important component, because if there is an error in this election could complicate efforts distribution of goods and services from producers to consumers.This study aimed to analyze the share, margins, and profits of manufacturers in every distribution channel of distribution channels and marketing efficiency sweet oranges in the District Dau, Malang as one of the centers of citrus production in East Java. This research is a quantitative research by questionnaire. Determination of respondents using stratified random sampling method of research. The division responen strata by strata of income. Variable observations in this study include marketing channels fruit sweet orange, the sales volume of citrus fruit once harvested (tonnes / ha), production costs incurred farmer (Rp / ha), the selling price (USD / ton), marketing costs (USD / Ha ) and the shrinkage of the product (Kg / year). Marketing efficiency oranges indicated parts prices received by farmers (25%) of the price of inputs, while 50% are owned by village traders (62.5%) value is the highest profit to retailers, amounting to Rp 3,000 to the value of margin is USD 2,328 and the value of the lowest profit are collectors of Rp 1,000 to Rp 827 margin value